Comparison of three manual ventilation devices using an intubated mannequin. Issue 6 (21st October 2004) - Hussey, S G; Ryan, C A; Murphy, B P
Abstract : Objective: To compare three devices for manual neonatal ventilation. Design: Participants performed a two minute period of ventilation using a self inflating device, an anaesthesia bag with attached manometer, and a Neopuff device. An intubated neonatal mannequin, approximating a 1 kg infant with functional lungs, was used for the study. Target ventilation variables included a rate of 40 breaths per minute, peak inspiratory pressure (PIP) of 20 cm H2 O, and positive end expiratory pressure (PEEP) of 4 cm H2 O. The circuit was attached to a laptop computer for data recording. Results: Thirty five participants were enrolled, including consultant neonatologists, paediatricians, and anaesthetists, paediatric and anaesthetic registrars, and neonatal nurses. The maximum PIP recorded using the self inflating bag, anaesthetic bag, and Neopuff device were 75.9, 35.5, and 22.4 cm H2 O respectively. There were significant differences between the devices for mean PIP (30.7, 18.1, and 20.1 cm H2 O), mean PEEP (0.2, 2.8, and 4.4 cm H2 O), mean airway pressure (7.6, 8.5, and 10.9 cm H2 O), % total breaths ⩽ 21 cm H2 O PIP (39%, 92%, and 98%), and % total breaths ⩾ 30 cm H2 O PIP (45%, 0, and 0). There was no difference between doctors and allied health professionals for the variables examined. Conclusion: The anaesthetic bag with manometer and Neopuff device both facilitate accurate and reproducible manual ventilation. Self inflating devices without modifications are not as consistent by comparison and should incorporate a manometer and a PEEP device, particularly when used for resuscitation of very low birthweight infants.